2018
DOI: 10.2147/ijgm.s184406
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of bactericidal action of amylmetacresol/2,4-dichlorobenzyl alcohol lozenges against oropharyngeal organisms implicated in pharyngitis

Abstract: PurposePharyngitis is commonly caused by a self-limiting upper respiratory tract infection (URTI) and symptoms typically include sore throat. Antibiotics are often inappropriately used for the treatment of pharyngitis, which can contribute to antimicrobial resistance, therefore non-antibiotic treatments which have broad antiseptic effects may be more appropriate. Amylmetacresol (AMC) and 2,4-dichlorobenzyl alcohol (DCBA) are present in some antiseptic lozenges and have established benefits in providing symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…In a similar in vitro study, Matthews et al (2018) reported that lozenges containing 0.6 mg amylmetacresol and 1.2 mg 2,4-dichlorobenzyl alcohol had broad antibacterial activity against a similar range of oropharyngeal organisms associated with acute sore throat. Specifically, reductions in bacterial counts exceeded 99.9% by 1 min for S. pyogenes, H. influenzae, F. necrophorum and A. haemolyticum, by 5 min for M. catarrhalis and S. dysgalactiae and by 10 min for S. aureus [21]. The antibacterial effects of hexylresorcinol lozenges reported here add to existing knowledge of their activity, which include numbing effects [13,14] and antiviral activity [16,17], resulting in relief of sore throat symptoms [13].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In a similar in vitro study, Matthews et al (2018) reported that lozenges containing 0.6 mg amylmetacresol and 1.2 mg 2,4-dichlorobenzyl alcohol had broad antibacterial activity against a similar range of oropharyngeal organisms associated with acute sore throat. Specifically, reductions in bacterial counts exceeded 99.9% by 1 min for S. pyogenes, H. influenzae, F. necrophorum and A. haemolyticum, by 5 min for M. catarrhalis and S. dysgalactiae and by 10 min for S. aureus [21]. The antibacterial effects of hexylresorcinol lozenges reported here add to existing knowledge of their activity, which include numbing effects [13,14] and antiviral activity [16,17], resulting in relief of sore throat symptoms [13].…”
Section: Discussionmentioning
confidence: 61%
“…Hexylresorcinol 2.4 mg lozenges (Strepsils Extra Honey and Lemon lozenges; Reckitt Benckiser, Slough, UK) were dissolved at 44 ± 1 ℃ into 5 mL of artificial saliva medium as described previously [21].…”
Section: Test Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…2,4-Дихлорбензиловий спирт (13) (рис. 4) інколи додають як бактерицидний засіб до зубних паст та пастилок для лікування фарингіту [96].…”
Section: ) спиртиunclassified